(untitled) (Fiep Bulletin - online, 2016)
Amputation is considered one of the oldest medical therapeutic resources and designates the total or partial removal of a body part. Objective: describe the characteristics of the amputee patients concerning age, gender, levels, amputations causes and if they have already received prostheses. Method: A cross, retrospective, descriptive study involving 156 amputee subjects treated for the first time at FAG’s Rehabilitation Centre in 2014. The data was collected and registered in spreadsheets in the program Microsoft Excel 2010. Results: The male gender represented 76.29% of the sampling. The average age was 53.33 years. 64% suffered amputation due to one or more pathologies and 36% due to traumatic processes. The most frequent age range in the clinical amputations was 60 to 79 years, while in the traumatic amputations the age varied from 20 to 39. As for the level of amputations, there was predominance in the transradial level in the upper limbs and transfemoral level, in the lower. Of the 156 amputees, 3 subjects had bilateral amputation and 109 had already received prosthesis at the end of that year. Conclusion: It was seen that the male population was the majority of the clinical amputations, traumatic amputations and in the most affected age group, except in the age range up to age 20, where it tied with the female gender. We believe that a project of this nature may contribute to the awareness about the need for taking care of your own health and warn that the causes and consequences of trauma almost always depend on human actions.